2016
DOI: 10.1152/japplphysiol.00175.2015
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture plus low-frequency electrical stimulation (Acu-LFES) attenuates denervation-induced muscle atrophy

Abstract: Muscle wasting occurs in a variety of clinical situations, including denervation. There is no effective pharmacological treatment for muscle wasting. In this study, we used a tibial nerve denervation model to test acupuncture plus low-frequency electric stimulation (Acu-LFES) as a therapeutic strategy for muscle atrophy. Acupuncture needles were connected to an SDZ-II electronic acupuncture device delivering pulses at 20 Hz and 1 mA; the treatment was 15 min daily for 2 wk. Acu-LFES prevented soleus and planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 55 publications
0
33
3
Order By: Relevance
“…For synthesis of cDNA, 10 ng of total RNA that was enriched in small RNAs was reverse transcribed using an NCode miRNA cDNA synthesis kit (Exiqon, Vedbaek, Denmark). The expression of microRNA was measured as described 46. Primers were purchased from Exiqon.…”
Section: Methodsmentioning
confidence: 99%
“…For synthesis of cDNA, 10 ng of total RNA that was enriched in small RNAs was reverse transcribed using an NCode miRNA cDNA synthesis kit (Exiqon, Vedbaek, Denmark). The expression of microRNA was measured as described 46. Primers were purchased from Exiqon.…”
Section: Methodsmentioning
confidence: 99%
“…We tested this in denervated muscles because denervation can cause muscle injury and atrophy, at same time trigger myogenic activity as a compensatory response[21]. In mice with unilateral sciatic denervation, we observed that UCHL1 protein level was significantly increased in denervated muscles as compared with the control muscles.…”
Section: Resultsmentioning
confidence: 99%
“…The LFES treatment was done on acupoint GB34 and ST36 of denervation-induced mice model. The results demonstrated that LFES stimulated expression of miR-1 and miR-206 as its expression was increased in the skeletal muscle [43].…”
Section: Main Textmentioning
confidence: 99%